Evaluation Analysis Study of the Integration of Islamic Values in Sociology Learning in Fostering Islamic Character - Hidayat, Tatang; Rizal, Ahmad Syamsu; Abdussalam, Aam; Kosasih, Aceng; Istianah, Istianah (Jurnal Sosiologi Pendidikan Humanis, 2024)
The discovery of a dichotomy between general science and religious science both in terms of theory and practice in the implementation of learning at the elementary / junior high school / high school / equivalent and university levels in Indonesia causes various problems. The purpose of this study is to find a hypothetical model of evaluating the integration of Islamic values in sociology learning in fostering Islamic character at SMA PGII 2 Bandung. This research uses a qualitative approach and descriptive method of case study types. The researcher acts as the main instrument. Data retrieval techniques with interviews, observations, and documentation studies. Data analysis techniques with data reduction, data coding, data display, interpretation of findings and drawing conclusions. Test the credibility of the data by extending the research time, increasing perseverance, triangulating data, using reference materials and focus group discussions. Based on the results of the study, the evaluation of the integration of Islamic values in sociology learning at SMA PGII 2 Bandung has not occurred comprehensively. The evaluation in sociology learning has been systematically planned. Aspects evaluated as well as planning in learning tools include aspects of attitudes, knowledge, and skills. The attitude evaluation instrument in sociology learning is almost the same as schools in general, namely using an attitude evaluation instrument based on the 2013 curriculum. However, in its implementation, the emphasis on evaluation is still dominant in the aspect of knowledge. The development of social attitudes and skills of students after participating in sociology learning integrated with Islamic values has not been felt thoroughly, because the attitudes assessed have not been integrated with ilāhiah values. On the other hand, the written evaluation of the integration of Islamic values in sociology learning at the level of material substance has not been integrated, because the teacher only evaluates the material as it is in the package book. Studi Analisis Evaluasi Integrasi Nilai-Nilai Islam pada Pembelajaran Sosiologi dalam Membina Karakter Islami Masih ditemukannya dikotomi antara ilmu umum dan ilmu agama baik dari segi teori dan praktek dalam pelaksanaan pembelajaran di jenjang SD/SMP/SMA/sederajat dan perguruan tinggi di Indonesia menyebabkan berbagai problematika. Tujuan penelitian ini untuk menemukan model hipotetik evaluasi integrasi nilai-nilai Islam pada pembelajaran sosiologi dalam membina karakter Islami di SMA PGII 2 Bandung. Penelitian ini menggunakan pendekatan kualitatif dan metode deskriptif jenis studi kasus. Peneliti bertindak sebagai instrument utama. Teknik pengambilan data dengan wawancara, observasi, dan studi dokumentasi. Teknik analisis data dengan reduksi data, koding data, display data, interpretasi temuan dan penarikan kesimpulan. Uji kredibilitas data dengan memperpanjang waktu penelitian, meningkatkan ketekunan, triangulasi data, menggunakan bahan referensi dan focus group discussion. Berdasarkan hasil penelitian, evaluasi integrasi nilai-nilai Islam pada pembelajaran sosiologi di SMA PGII 2 Bandung belum terjadi secara komprehensif. Adapun evaluasi dalam pembelajaran sosiologi sudah direncanakan secara sistematis. Aspek yang dievaluasi sebagaimana perencanaan yang ada dalam perangkat pembelajaran mencakup aspek sikap, pengetahuan, dan keterampilan. Instrumen evaluasi sikap pada pembelajaran sosiologi hampir sama dengan sekolah pada umumnya, yakni menggunakan instrumen evaluasi sikap berdasarkan kurikulum 2013. Namun dalam pelaksanaannya, penekanan evaluasi masih dominan aspek pengetahuan. Perkembangan sikap sosial dan keterampilan peserta didik setelah mengikuti pembelajaran sosiologi yang diintegrasikan dengan nilai-nilai Islam belum terasa secara menyeluruh, karena sikap yang dinilai belum terintegrasi dengan nilai-nilai ilāhiah. Di sisi lain, evaluasi tertulis integrasi nilai-nilai Islam pada pembelajaran sosiologi dalam tataran substansi materi belum terintegrasi, karena guru hanya mengevaluasi materi sebagaimana yang ada dalam buku paket.